2018
DOI: 10.1002/ajh.25370
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term improvement in cardiac magnetic resonance in β‐thalassemia major patients treated with deferasirox extends to patients with abnormal baseline cardiac function

Abstract: The management of iron overload in thalassemia has changed dramatically since the implementation of magnetic resonance imaging, which allows detection of preclinical iron overload and prevention of clinical complications. This study evaluated the effect of deferasirox (DFX), the newest once‐daily oral chelator, on cardiac function, iron overload and cardiovascular events over a longer follow up in a “real world” setting. Longitudinal changes in cardiac magnetic resonance T2*, cardiac function parameters and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Carpenter et al reported a worldwide survey of cardiac MR T 2 * that shows a moderate or severe cardiac iron overload condition at initial cardiac MR scanning 1 . To avoid this condition, early detection of iron loading by T 2 * measurement is needed and followed by an appropriate iron chelation therapy to improve the survival rate of hemochromatosis and transfusion‐dependent anemia patients 15,30,73,74 . Several studies reported a reduction of age recommendation to start the first T 2 * screening for thalassemia major patients from 10 years old to as early as 5 years old.…”
Section: Clinical Application Of T2* Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…Carpenter et al reported a worldwide survey of cardiac MR T 2 * that shows a moderate or severe cardiac iron overload condition at initial cardiac MR scanning 1 . To avoid this condition, early detection of iron loading by T 2 * measurement is needed and followed by an appropriate iron chelation therapy to improve the survival rate of hemochromatosis and transfusion‐dependent anemia patients 15,30,73,74 . Several studies reported a reduction of age recommendation to start the first T 2 * screening for thalassemia major patients from 10 years old to as early as 5 years old.…”
Section: Clinical Application Of T2* Mappingmentioning
confidence: 99%
“…1 To avoid this condition, early detection of iron loading by T 2 * measurement is needed and followed by an appropriate iron chelation therapy to improve the survival rate of hemochromatosis and transfusion-dependent anemia patients. 15,30,73,74 Several studies reported a reduction of age recommendation to start the first T 2 * screening for thalassemia major patients from 10 years old to as early as 5 years old. The reduction promotes early detection of iron loading in pediatric patients.…”
Section: Clinical Application Of T 2 * Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…The available treatment for this condition is iron chelation therapy, which has been shown to slow cardiac dysfunction and reduce mortality . As recent research shows, the beneficial effects of iron chelation extend even to patients with evident baseline cardiac dysfunction …”
Section: Role Of Iron In Heart Diseasementioning
confidence: 99%